An analytical study of gender equality in the Mappadendang tradition - Prasetio, Tri Bambang; Amin, Sitti Jamilah; Wahidin, Abd (Program Studi Tadris IPS Institut Agama Islam Negeri (IAIN) Parepare, 2024)
The Mappadendang tradition, as one of the cultural heritage of the Bugis people in South Sulawesi, plays an important role in maintaining the preservation of cultural and social values. This research aims to analyze gender equality in the context of the implementation of the Mappadendang tradition. Using a qualitative approach to explore gender perceptions and participation. Data collection was carried out through in-depth interviews with 18 informants consisting of traditional actors, community leaders, and regional policymakers in the Wattang Bacukiki Village. Data analysis was carried out by applying Fatimah Mernissi's Islamic Feminism theory, with a focus on narrative interpretation to identify and understand aspects of gender equality in traditional practices. The results show how important female figures are in the Mappadendang tradition in social, cultural, and religious contexts. This tradition also reflects gender equality with active and alternating participation between men and women in the preparation and implementation of the tradition. This research highlights the active role of Muslim women in caring for and preserving cultural heritage. Mappadendang creates an inclusive environment without boundaries of difference, supports gender equality, and is an example of women's empowerment. Overall, this tradition reflects how the principles of Islamic feminism shape and strengthen gender equality in everyday life as well as the implementation of local traditions that are categorized as gender responsive. Full support from the community and government is needed to maintain sustainability and local values, especially in the context of the Mappadendang tradition.